1993
DOI: 10.1159/000187407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parathyroid-Hormone-Related Protein on Sodium-Dependent Phosphate Transport in Renal Brush Border Membrane Vesicles in Rats

Abstract: Parathyroid-hormone-related protein (PTHrP) has significant homology with parathyroid hormone (PTH) in the amino-terminal region. We compared the effects of synthetic human PTHrP [hPTHrP(1-34)] on Na+-dependent phosphate transport with those of synthetic human PTH [hPTH(1-34)]. Intravenous administration of hPTHrP(1-34) in parathyroidectomized rats caused hypercalcemia, hypophosphatemia and phosphaturia to the same degree as hPTH(1-34). In kinetic studies using renal brush border membrane vesicles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…We also found no differences in the renal abundance of the FGF23 co-receptor, α-Klotho, at any time point and in any group (Figure S3A-F). Due to a possible impact of PTHrp on renal Pi reabsorption, as reported in several species, 29,34,35 we measured the plasma levels of this hormone. PTHrp levels were not altered by Pi gavage, though 4 h after gavage differences between genotypes were observed (Figure 2G-I).…”
Section: Induction Of Pth and Fgf23 In Response To Acute Pi Gavagementioning
confidence: 99%
“…We also found no differences in the renal abundance of the FGF23 co-receptor, α-Klotho, at any time point and in any group (Figure S3A-F). Due to a possible impact of PTHrp on renal Pi reabsorption, as reported in several species, 29,34,35 we measured the plasma levels of this hormone. PTHrp levels were not altered by Pi gavage, though 4 h after gavage differences between genotypes were observed (Figure 2G-I).…”
Section: Induction Of Pth and Fgf23 In Response To Acute Pi Gavagementioning
confidence: 99%
“…PTHi stimulates the reabsorption of calcium in the proximal convoluted tubule and stimulates calcium reab sorption against an electrochemical gradient in the distal tubule. After the administration of PTHi in vivo, the Vmax of the sodium-calcium exchanger in subsequently iso lated basolateral membrane vesicles is significantly in creased [37,38], Several studies have demonstrated that l,25(OH)2 cholecalcipherol could normalize intracellu lar calcium through lowering PTHi secretion in uremic patients with secondary hyperparathyroidism [33,39], The reduction in serum PTHi levels in response to 1 ,25(OH)2D i is presumed to be due to an increase in plas ma calcium, and direct suppression of PTHi synthesis secretion, especially after intravenous administration [14,40],…”
Section: Discussionmentioning
confidence: 99%
“…PTH-related protein (PTHrP) exerts effects similar to the inhibitory action of PTH on renal Pi uptake by isolated brush border membrane vesicles (Muff, Caulfield, & Fischer, 1990;Saito, Hirano, Kubota, Tomino, & Koide, 1993). The biological importance of this action to the normal economy of phosphate is not known.…”
Section: Pka/pkc Inhibitorsmentioning
confidence: 99%